2007
DOI: 10.1038/sj.eye.6702889
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection: new pharmacological targets

Abstract: Recent research in the field of neuroprotection in glaucoma has focused on the N-methyl-D-aspartate (NMDA) and the a-2 adrenergic receptor systems. Experimental findings have shown that brimonidine (BMD), a specific a-2 adrenoceptor agonist, can protect against loss in mitochondrial membrane potential during oxidative stress, and preserve anterograde axonal transport. Memantine is a selective blocker of the NMDA-type glutamatergic type ion channel. It has unique open channel blocker properties that result in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Wheeler et al found that brimonidine could send signals that protect the mitochondria during oxidative stress (Wheeler et al, 2007). In the current study, we demonstrated that brimonidine inhibited H 2 O 2 -induced up-regulation of Bax, Caspase-9 and Caspase-3, increased the expression of Bcl-2, accompanied with up-regulation of a 2b -AR subtype.…”
Section: Discussionmentioning
confidence: 50%
“…Wheeler et al found that brimonidine could send signals that protect the mitochondria during oxidative stress (Wheeler et al, 2007). In the current study, we demonstrated that brimonidine inhibited H 2 O 2 -induced up-regulation of Bax, Caspase-9 and Caspase-3, increased the expression of Bcl-2, accompanied with up-regulation of a 2b -AR subtype.…”
Section: Discussionmentioning
confidence: 50%
“…The mechanism of UK‐14,304’s protective effect is not yet completely understood. It is known that alpha2‐adrenergic receptor stimulation can activate the anti‐apoptotic phosphatidylinositide 3 kinase/protein kinase B (PI3 kinase/Akt) signal transduction pathway (Wheeler et al. 2007).…”
mentioning
confidence: 99%
“…The mechanism of UK-14,304's protective effect is not yet completely understood. It is known that alpha2-adrenergic receptor stimulation can activate the anti-apoptotic phosphatidylinositide 3 kinase/protein kinase B (PI3 kinase/Akt) signal transduction pathway (Wheeler et al 2007). To test which pathway is activated by UK-14,304, we also tested the effect of 304 in the presence of 2-(4-morpholinyl)-8phenyl-4H-1-benzopyran-4-one (Ly 294002), a PI3 kinase inhibitor.…”
mentioning
confidence: 99%